DEVELOPMENT OF SIBHOTIK MOTIF DESIGNS, ACCOUNTING BOOKKEEPING AND DIGITAL MARKETING IN SMALL AND MEDIUM-SIZED ENTERPRISES (SMEs) - Hatta, Atika Jauharia; Kusumawati, Toyibah; Marwanta, Y. Yohakim; Indraswono, Cahyo; Kurniawati, Anggreni Dian (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2025)
The aim of this community service is to improve the capabilities of the Wijayakusuma batik group SMEs in developing shibotik motif designs, accounting bookkeeping for recording transactions, and digital marketing using internet websites. This SME is in Ngandong village, Gantiwarno subdistrict, Klaten, chaired by Ms. Wijayanti. This group has several priority problems that must be resolved, including: fabric motif designs that are still monotonous and less attractive, bookkeeping that does not exist or financial records are still very simple, and marketing that is still traditional, namely only by word of mouth. The solution then provided by the community service to overcome this problem was to provide batik design training on shibori which is known as Shibotik, simple accounting bookkeeping training for SMEs either manually or simply computerized, as well as internet website development and training for marketing. The method approach applied is participatory training and supervision, partners will always be involved in every activity process. The output that has been achieved in this service is batik motifs applied to shibori, a simple accounting system for SMEs, and an internet website for marketing. With this training, partners are expected to have good skills and abilities in financial management, production and marketing.